Currency Substitution and Inflation in Peru - Rojas-Suarez, Liliana (Washington, D.C. : International Monetary Fund, 1992)
This paper shows that there is a long-run relationship between the expected rate of depreciation in the black-market-exchange rate and the ratio of domestic to foreign money in Peru; that is, the hypothesis of currency substitution can explain the behavior of real holdings of money in Peru. The paper also shows that, while the importance of currency substitution as a transmission mechanism through which domestic policies affected the dynamics of inflation was relatively small during a period of high but relatively stable inflation (January 1978-85), it became an important factor in the inflation process during the recent hyperinflation episode.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet